The Effect of Discontinuing Treatment With Blosozumab: Follow‐up Results of a Phase 2 Randomized Clinical Trial in Postmenopausal Women With Low Bone Mineral Density. (11th June 2015) - Recknor, Christopher P; Recker, Robert R; Benson, Charles T; Robins, Deborah A; Chiang, Alan Y; Alam, Jahangir; Hu, Leijun; Matsumoto, Toshio; Sowa, Hideaki; Sloan, John H; Konrad, Robert J; Mitlak, Bruce H; et al.
ABSTRACT: Administration of blosozumab, a humanized monoclonal antibody that binds sclerostin, increases bone formation and bone mineral density (BMD) in postmenopausal women with low BMD. To evaluate the effect of discontinuing blosozumab, we studied women enrolled in a 1‐year randomized, placebo‐controlled phase 2 trial for an additional year after they completed treatment. Of the 120 women initially enrolled in the study, 106 women completed treatment and continued into follow‐up; 88 women completed 1 year of follow‐up. At the beginning of follow‐up, groups remained balanced for age, race, and body mass index, but lumbar spine and total hip BMD were increased in prior blosozumab groups, reflecting an anabolic treatment effect. At the end of follow‐up, 1 year after discontinuing treatment, lumbar spine BMD remained significantly greater than placebo in women initially treated with blosozumab 270 mg every 2 weeks (Q2W) and blosozumab 180 mg Q2W (6.9% and 3.6% above baseline, respectively). Total hip BMD also declined after discontinuation of treatment but at 1 year after treatment remained significantly greater than placebo in women initially treated with blosozumab 270 mg Q2W and blosozumab 180 mg Q2W (3.9% and 2.6% above baseline, respectively). During follow‐up, median serum P1NP was not consistently different between the prior blosozumab groups and placebo. A similar pattern was apparent for median serum C‐terminal telopeptide of type 1 collagen (CTx) levels, with more variability. Mean serum total sclerostin concentration increased with blosozumab, indicating target engagement, and declined to baseline after discontinuation. There were no adverse events considered related to prior treatment with blosozumab. Anti‐drug antibodies generally declined in patients who had detectable levels during prior treatment. These findings support the continued study of blosozumab as an anabolic therapy for treatment of osteoporosis. © 2015 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research (ASBMR).